A CHILDREN ACTIVITY SPACE IN MEDAN: WAKE FROM SCREENS, LIVE THE SCENE - Novi Rahmadhani; Melinda Elisabeth Tambunan (CV. Denasya Smart Publisher, 2026)
The increasing dependence on gadgets among children has led to reduced physical activity, limited social interaction, and diminished engagement with the real world. In urban contexts such as Medan, this condition calls for architectural interventions that function as preventive environments. This study proposes a Children Activity Space in Medan: Wake from Screens, Live the Scene, a facility designed to encourage children to disengage from excessive screen use and actively reconnect with real-life experiences. The design applies a Behavior Architecture approach, utilizing spatial configuration as a tool to influence and shape positive behavioral patterns. Through the integration of active play areas, recreational spaces, sensory-based activities, and psychological support facilities, the building promotes movement, social interaction, and environmental awareness. Spatial zoning and activity-oriented layouts are strategically arranged to reduce passive behavior associated with gadget use. The study demonstrates that architecture can serve as an effective preventive strategy in reducing gadget dependence and fostering active, healthy play behaviors in children.